2007
DOI: 10.1073/pnas.0704940104
|View full text |Cite|
|
Sign up to set email alerts
|

Increased prostate cell proliferation and loss of cell differentiation in mice lacking prostate epithelial androgen receptor

Abstract: Developmental studies of the prostate have established that ductal morphogenesis, epithelial cytodifferentiation, and proliferation/apoptosis are regulated by androgens acting through stromal androgen receptor (AR). Here, we found mice lacking epithelial AR within the mature prostate (pes-ARKO) developed prostate tissue that was less differentiated and hyperproliferative relative to WT littermates. Epithelial AR protein was significantly decreased in 6-week-old mice and was nearly absent by ≥24 weeks of age. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
175
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 183 publications
(186 citation statements)
references
References 38 publications
11
175
0
Order By: Relevance
“…In this TRAMP mouse, the prostate progressively develops from early prostatic epithelial neoplasia (PIN) to metastatic Pca, which mimics the pathological progression of human PCa. To study the prostatic epithelial AR function in TRAMP mice, we generated pes-ARKO-TRAMP compound mouse [38,72,79]. pes-ARKO-TRAMP mice spontaneously develop PCa, and progressively and simultaneously knock out epithelial AR.…”
Section: Available Genetically Engineered Mouse (Gem) Models For Pca mentioning
confidence: 99%
See 1 more Smart Citation
“…In this TRAMP mouse, the prostate progressively develops from early prostatic epithelial neoplasia (PIN) to metastatic Pca, which mimics the pathological progression of human PCa. To study the prostatic epithelial AR function in TRAMP mice, we generated pes-ARKO-TRAMP compound mouse [38,72,79]. pes-ARKO-TRAMP mice spontaneously develop PCa, and progressively and simultaneously knock out epithelial AR.…”
Section: Available Genetically Engineered Mouse (Gem) Models For Pca mentioning
confidence: 99%
“…These models could more closely mimic human PCa progression and metastasis by considering the stromal factors and extra-cellular microenvironments. With the rapid development of transgenic technology, some spontaneous PCa mouse models [78,82,87] and prostate-specific AR knockout mouse models [38,72,79] have also been well established. These models might yield important contributions and revolutionize research on AR and PCa.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Once the mature size of the prostate is reached, it remains quiescent even in the presence of stimulating physiological levels of androgens (Simanainen et al, 2007;Wu et al, 2007). In PCa, however, epithelial cells develop alternate mechanisms of escaping growth inhibition in the presence of androgens and proliferate, resulting in excessive growth.…”
Section: Cross-talk Between Androgen Receptors and Egfr Signalling Pamentioning
confidence: 99%
“…Further comparison between pes-ERaKO and WT prostates was conducted on 12-month-old mice, since PB-Cre efficiency is believed to reach 100% at that age. 38 Comparisons revealed that pes-ERaKO and WT prostates have similar gene expression profiles and branching morphogenesis (data not shown). Taken together, our findings suggest that stromal ERa, but not epithelial ERa, is involved in prostatic branching morphogenesis and homeostasis of prostate.…”
Section: Generation and Genotyping Of Pes-erako Micementioning
confidence: 96%
“…The promoter of probasin is well characterized and widely applied in many animal models. [37][38][39] The expression of probasin Cre (PB-Cre) is prostatic epithelial-specific and is postnatal and gradually increased with highest expression in the lateral lobe, followed by the VP, and then the DP and AP. 37,38 Therefore, PB-Cre can specifically knock out the floxed ERa gene in prostate epithelial cells (pes-ERaKO).…”
Section: Generation and Genotyping Of Pes-erako Micementioning
confidence: 99%